A Practical Guide for Anesthesia Providers on the Management of Coronavirus Disease 2019 Patients in the Acute Care Hospital. (26th October 2020) - Abola, Ramon E.; Schwartz, Jonathan A.; Forrester, Joseph D.; Gan, Tong J.
Abstract : The coronavirus disease 2019 (COVID-19) pandemic has infected millions of individuals and posed unprecedented challenges to health care systems. Acute care hospitals have been forced to expand hospital and intensive care capacity and deal with shortages in personal protective equipment. This guide will review 2 areas where the anesthesiologists will be caring for COVID-19 patients: the operating room and on airway teams. General principles for COVID-19 preparation and hospital procedures will be reviewed to serve as a resource for anesthesia departments to manage COVID-19 or future pandemics.